2022
DOI: 10.3390/ma15196886
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bobbin Tool Friction Stir Processing Parameters of AA1050 Using Response Surface Methodology

Abstract: The current research designed a statistical model for the bobbin tool friction stir processing (BT-FSP) of AA1050 aluminum alloy using the Response Surface Method (RSM). The analysis studied the influence of tool travel speeds of 100, 200, and 300 mm/min and different pin geometries (triangle, square, and cylindrical) at a constant tool rotation speed (RS) of 600 rpm on processing 8 mm thickness AA1050. The developed mathematical model optimizes the effect of the applied BT-FSP parameters on machine torque, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…As a result, the low p -value (less than .05) shows that the model is significant at a 95% confidence level. 22 According to the ANOVA analysis, Fisher’s F-test results with a high F-value and low p -value indicated that the models were highly significant. The coefficient of determination (R 2 ) is analyzed as the ratio of the variability in the data described by the ANOVA analysis and defined in equation (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the low p -value (less than .05) shows that the model is significant at a 95% confidence level. 22 According to the ANOVA analysis, Fisher’s F-test results with a high F-value and low p -value indicated that the models were highly significant. The coefficient of determination (R 2 ) is analyzed as the ratio of the variability in the data described by the ANOVA analysis and defined in equation (6).…”
Section: Resultsmentioning
confidence: 99%
“…The design of experiments (DOE) is an efficient approach for studying the effect of control parameters and their interaction on the performance of the process output. 21,22 The traditional experimental technique is challenging, mainly when many experimentations and process parameters are required. 23,24 The essential step in the DOE is setting the control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The deformed material is moved around the probe from the leading to the trailing edge (TA) and deposited beneath the shoulder. 2,3 FSP is a versatile technique for repairing casting defects, 4 local modifications of microstructure, 5 achieving grain refinement, 6 and producing surface composites in metals and alloys. 7 To accomplish these functions, singlepass FSP is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The deformed material is moved around the probe from the leading to the trailing edge (TA) and deposited beneath the shoulder. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…The maximum joint efficiency obtained was 80% [122]. Ahmed et al [58,[127][128][129][130] conducted several studies investigating the effect of the tool pin profile and traversal speed mechanical properties of aluminum alloys. Their The performance of the high-strength aluminum alloys was investigated after welding using BTFSW and compared with that welded by the conventional FSW (CFSW) [121][122][123][124][125][126].…”
mentioning
confidence: 99%